Mettl14-mediated m6A modification enhances the function of Foxp3+ regulatory T cells and promotes allograft acceptance - Liu, Yanzhuo; Yuan, Yinglin; Zhou, Zili; Cui, Yuanyuan; Teng, Yan; Huang, Hao; Yuan, Hao; Zhang, Yanling; Yang, Lu; Zhao, Gaoping (Frontiers in Immunology, 2022)
N6-methyladenosine (m6A), the most prevalent form of internal mRNA modification, is extensively involved in Treg cells differentiation and function. However, the involvement of m6A in functional Treg cells for transplantation tolerance remains to be elucidated. By using an experimental transplantation mouse model, we found that m6A levels in Treg cells were altered during the induction of transplant tolerance by performing a dot blotting assay. Subsequently, we used the heterogenic Treg-specific Mettl14 knockout mice (Foxp3-Mettl14f/+ cKO) to reduce METTL14 expression and performed islets allograft transplantation. Our result revealed that reduced expression of METTL14 prevented Treg cells expansion and promoted the infiltration of CD4+ and CD8+ T cells around the allograft, which led to rapid allograft rejection in Foxp3-Mettl14f/+ cKO mice. The expression of regulatory cytokines including IL-10 and TGF-β was significantly decreased in Foxp3-Mettl14f/+ cKO mice, and the suppressive function of Treg cells was also abrogated. In addition, an analysis of RNA-seq data revealed that the SOCS family (SOCS1, SOCS2 and SOCS3) is the subsequent signaling pathway affected by the METTL14 mediated m6A modification in Treg cells to modulate the suppressive function after transplantation. Taken together, our study showed for the first time that the METTL14-mediated m6A modification is essential for the suppressive function of Treg cells in transplantation and may serve as a regulatory element of Treg cell-based therapy in transplant medicine.